Valorization of the Invasive Fish Atherina boyeri (Risso, 1810) as a Source of Protein Hydrolysates with Functional and Bioactive Properties - Kizilkoy, Irem Ceren; Tekle, Sefik; Bozkurt, Fatih; Goktas, Hamza; Ozcan, Fahriye Seyma; Yilmaz, Mahmut; Sagdic, Osman (MDPI, 2026)
The invasive fish Atherina boyeri constitutes an ecologically disruptive yet underexploited biomass with strong potential for transformation into value-added biofunctional ingredients. This study investigates the functional, antioxidant, and antimicrobial properties of protein hydrolysates that were produced from fish collected in the Hirfanl & imath; and Yamula reservoirs using three commercial proteases (alcalase, bromelain, and flavourzyme). Bromelain produced the highest degree of hydrolysis, yielding higher proportions of low-molecular-weight peptides and greater radical-scavenging activity. Flavourzyme hydrolysates exhibited the most favorable emulsifying properties, Alcalase hydrolysates produced the highest foaming capacity and stability. All hydrolysates showed high absolute zeta-potential values across pH 3-9, demonstrating strong colloidal stability. Protein solubility remained above 80% across most pH levels, indicating extensive peptide release and improved compatibility with aqueous media. The Oil-binding capacity (2.78-3.75 mL/g) was consistent with reported values for marine hydrolysates. Antioxidant and antimicrobial evaluations revealed clear enzyme-dependent patterns, with Bromelain exhibiting the strongest DPPH activity and Alcalase and Flavourzyme showing the most pronounced inhibition of major foodborne pathogens. Additionally, all hydrolysates exhibited measurable ACE-inhibitory activity, with flavourzyme-derived peptides showing the highest inhibitory activity, underscoring their potential relevance for antihypertensive applications. These findings highlight the strategic valorization of A. boyeri through enzymatic hydrolysis, demonstrating its potential as a sustainable, clean-label functional ingredient source.
Keywords: invasive species valorization; sustainable protein sources; protein hydrolysates; antioxidant activity; techno-functional properties; AMINO-ACID-COMPOSITION; ANTIOXIDANT; PEPTIDES; SALMON; Food Science & Technology